Analisis SWOT untuk Peningkatan Jumlah Santri Baru: Studi di Yayasan Pesantren Darut Taqwa Mojokerto - Qulub, Layyinul (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
The purpose of this research is to describe marketing strategies in increasing the quantity of new students at the Darut Taqwa Islamic Boarding School Foundation. The informants in the study were divided into two, namely the head of the foundation as the representative of the caretaker of the Darut Taqwa Islamic boarding school to H. Agus Sutikno, 40 years old, who lives in Ds. Ngembeh, Dlanggu, Mojokerto and as the head of the Darut Taqwa Islamic boarding school to ustadzh Muhammad Jakfar who is 26 years old residing in the islamic boarding school. Data analysis was performed by SWOT analysis. The results showed that the marketing strategy in increasing the quantity of new students at the Darut Taqwa Islamic Boarding School Foundation is to: a) Continue to promote both manually and by utilizing social media. This is done considering the coverage of students of the Darut Taqwa Islamic Boarding School Foundation, not only the area around the Darut Taqwa and Mojokerto Pesantren Foundations; b) Increase response on the website, social media or contact person of the Darut Taqwa Islamic Boarding School Foundation. This is done so that prospective students or parents of prospective students feel valued and get a good impression from the Darut Taqwa Islamic Boarding School Foundation; c) Increase activities in both religious and extracurricular fields at the Darut Taqwa Islamic Boarding School Foundation; and d) Increase the study of the yellow book and other books considering that the Darut Taqwa Islamic Boarding School Foundation has many competent ustazd/ustadzah as well as religious experts. This is done to attract prospective students and parents of prospective students so that their parties are interested in entering or including their children in competent ustazd / ustadzah.